2017
DOI: 10.1073/pnas.1708097114
|View full text |Cite
|
Sign up to set email alerts
|

Host-derived viral transporter protein for nitrogen uptake in infected marine phytoplankton

Abstract: Phytoplankton community structure is shaped by both bottomup factors, such as nutrient availability, and top-down processes, such as predation. Here we show that marine viruses can blur these distinctions, being able to amend how host cells acquire nutrients from their environment while also predating and lysing their algal hosts. Viral genomes often encode genes derived from their host. These genes may allow the virus to manipulate host metabolism to improve viral fitness. We identify in the genome of a phyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 105 publications
2
83
0
1
Order By: Relevance
“…We know of several mechanisms for the introduction of foreign DNA into eukaryotic genomes, and we have direct evidence for some of them occurring on a recent time scale. Eukaryotic genomes are littered with remnants of viruses and transposons that promiscuously hop between diverse eukaryotic host genomes, sometimes mobilizing host DNA in the process . Conjugation between bacteria and eukaryotes in nature is well documented and can be reproduced under laboratory conditions (reviewed in ref.…”
Section: Mechanisms and Evidence Of Lateral Gene Transfer In Eukaryotesmentioning
confidence: 99%
“…We know of several mechanisms for the introduction of foreign DNA into eukaryotic genomes, and we have direct evidence for some of them occurring on a recent time scale. Eukaryotic genomes are littered with remnants of viruses and transposons that promiscuously hop between diverse eukaryotic host genomes, sometimes mobilizing host DNA in the process . Conjugation between bacteria and eukaryotes in nature is well documented and can be reproduced under laboratory conditions (reviewed in ref.…”
Section: Mechanisms and Evidence Of Lateral Gene Transfer In Eukaryotesmentioning
confidence: 99%
“…Many phage contain auxiliary metabolic genes that modify a host's resource allocation (Monier et al . ). For example, phage‐encoded genes for phosphorus acquisition ( pstS and phoA ) were upregulated when phosphorus‐starved marine Prochlorococcus was infected by phage P‐SSM2 (Zeng & Chisholm ).…”
Section: Discussionmentioning
confidence: 97%
“…We designed probes to detect OtV5, but the alignment of the probes with other Prasinovirus genomes showed that they can very likely label all 11 genome sequenced Ostreococcus spp. viruses (Table S2 and Table S3), except OtV6, which is evolutionarily distinct (Monier et al , 2017). Thus, our technique may help in fostering our knowledge on the role of viruses in the control of the abundance of the cosmopolitan Ostreococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Currently available methods to assess the dynamics between host and viruses during infection are i) the frequency of visibly infected cells (FVIC) (Wommack and Colwell, 2000), ii) Real Time PCR (RT-PCR) (Monier et al , 2017) of viral genes and iii) the plaque assay, for counting plaque forming units (PFU) (Brussaard et al , 2016). Compared with these methods, VirusFISH brings further advantages.…”
Section: Discussionmentioning
confidence: 99%